Answer:
Option A is correct.
i.e. x = 1, x = 0 is an extraneous solution.
Explanation:
Given the expression
![(5)/(x)=(4x+1)/(x^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9n8us8v9rqfuzx262kfi5jc9gfj6s0hk47.png)
Solving the rational function
![(5)/(x)=(4x+1)/(x^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9n8us8v9rqfuzx262kfi5jc9gfj6s0hk47.png)
Apply fraction across multiply: if
![(a)/(b)=(c)/(d)\mathrm{\:then\:}a\cdot \:d=b\cdot \:c](https://img.qammunity.org/2022/formulas/mathematics/high-school/5v1dglcb80yhmy76s5ysdi7p41xt66ucnw.png)
![5x^2=x\left(4x+1\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/i3um6zaemar5t0ezuxzgir2q4yh6ayf97x.png)
Subtract x(4x+1) from both sides
![5x^2-x\left(4x+1\right)=x\left(4x+1\right)-x\left(4x+1\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/iby34yig2cifhpux4en79s3mdqi7xv7ysw.png)
Simplify
![5x^2-x\left(4x+1\right)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/50iy292kav9ripid0yydipqek6f92fiq4a.png)
5x² - 4x² - x = 0
x² - x = 0
Factor x² - x = x(x-1)
so
x(x-1) = 0
Using the zero factor principle
if ab=0, then a=0 or b=0 (or both a=0 and b=0)
![x=0\quad \mathrm{or}\quad \:x-1=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/qcgqkfs0k3rgqmx6vqqzof2o68h1ag72e4.png)
Thus, the solution to the equation is:
![x=0,\:x=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/sti92xgxorvnbv1zwzdq1473jn9utgg2t0.png)
But, it is clear that if we substitute x = 0, the equation becomes undefined because we can not have the denominator to be 0.
In other words, the equation is undefined for x = 0
Thus, x = 0 is an extraneous solutions.
Therefore, option A is correct.
i.e. x = 1, x = 0 is an extraneous solution.